Making a Homeland Roots and Routes of Transnational Armenian Engagement - Darieva, Tsypylma (Global Studies, 2023)
Ties to the homeland have always been a central focus of global diaspora and migration studies. How and why do the descendants of migrants maintain their attachment to the ancestral homeland? To what extent do emotional ties bind second and later generations of migrants to that place? Tsypylma Darieva examines various actors, channels and sites of transnational Armenian engagement that generate new pathways of diasporic ›roots‹ mobility. Drawing on long-term ethnographic observations in Armenia and in the USA, she examines transnational flows of people, money and ideas to show the social and political significance that roots mobility acquires when the mythical ›homeland‹ becomes a real place.